2015
DOI: 10.1088/1367-2630/18/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Bounding quantum gate error rate based on reported average fidelity

Abstract: Remarkable experimental advances in quantum computing are exemplified by recent announcements of impressive average gate fidelities exceeding 99.9% for single-qubit gates and 99% for two-qubit gates. Although these high numbers engender optimism that fault-tolerant quantum computing is within reach, the connection of average gate fidelity with fault-tolerance requirements is not direct. Here we use reported average gate fidelity to determine an upper bound on the quantum-gate error rate, which is the appropria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 48 publications
(105 reference statements)
1
133
1
Order By: Relevance
“…Note that we always find η ♦ η Pauli ♦ , so the dominant errors are non-Pauli errors and belong to the "bad" class of errors [33]. Interestingly, there is almost one order of magnitude difference between the actual error rate η ♦ and the optimal bounds η Pauli ♦ and η ub ♦ calculated from the gate fidelity F avg according to Eqs.…”
Section: A Gate Metricsmentioning
confidence: 86%
See 3 more Smart Citations
“…Note that we always find η ♦ η Pauli ♦ , so the dominant errors are non-Pauli errors and belong to the "bad" class of errors [33]. Interestingly, there is almost one order of magnitude difference between the actual error rate η ♦ and the optimal bounds η Pauli ♦ and η ub ♦ calculated from the gate fidelity F avg according to Eqs.…”
Section: A Gate Metricsmentioning
confidence: 86%
“…We have found that gate metrics such as the average gate fidelity [9], the diamond distance [10,33], and the unitarity [11] each provide insights into the errors of the implemented gate pulses. Specifically, while the time evolution of the total system is inherently unitary and the errors are systematic, they appear as incoherent non-Pauli errors on the computational subspace.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, for increasing σ in the pulse-area error model, the distribution rises from small P ψ+1 fail , with the most likely values scaling as σ 4 . We conjecture that the heavy tails in the pulse-area error model distribution are an indicator of the strongly negative impact that purely coherent errors can have on QEC [16,17].…”
Section: Discussionmentioning
confidence: 95%